Methicillin-resistant Staphylococcus aureus in Brazil: classification of SCCmec and virulence factors - Pimenta Rodrigues, M. V. [UNESP]; Sena Martins de Souza, C. [UNESP]; Teixeira, N. B. [UNESP]; Castelo Branco Fortaleza, C. M.; Ribeiro de Souza da Cunha, M. L. [UNESP]; MendezVilas, A. (World Scientific Publ Co Pte Ltd, 2011)
The objective this study was to detect methicillin-resistant Staphylococcus aureus (MRSA) in clinical and/or surveillance cultures of patients seen at a Brazilian teaching hospital and to associate their detection with the prevalence of resistance and virulence factors. The genotypic resistance and virulence profiles of 212 S. aureus strains were analyzed by PCR for detection of the mecA gene and positive strains were subtyped for the staphylococcal cassette chromosome (SCCmec) by multiplex PCR. Investigation of the mecA gene revealed 134 (63.2%) MRSA strains and the characterization of SCCmec showed the presence of SCCmec type III or variations of type III in 104 (77.6%) strains, SCCmec type I or IA in 23 (17.2%), SCCmec type IV in 4 (3%), and SCCmec type II in 3 (2.2%). Analysis of the virulence profile showed no significant difference in the presence of genes encoding biofilm production (icaA and/or icaD), delta hemolysin (hld), alpha hemolysin (hla), or enterotoxin A (sea) or B (seb) between MRSA and MSSA. However, the enterotoxin C gene (sec-I) was more frequent in MRSA strains.
Keywords: Staphylococcus aureus; MRSA; SCCmec; biofilm; toxins; virulence factors